An integrated biomarker response study explains more than the sum of the parts: Oxidative stress in the fish Australoheros facetus exposed to imidacloprid - Iturburu, Fernando Gastón (2018)
Integrated Biomarkers Response (IBR) index have been developed as a practical and robust tool to assess the susceptibility to pollutants using multiple biomarker responses. Neonicotinoid insecticides are nowadays one of the most sold pesticides worldwide. Nevertheless, imidacloprid (IMI) sub-lethal effects such as oxidative stress (OS) on fishes are scarcely studied. Hence, the aims of this work were: (1) to evaluate exposure- and damage biomarkers related to OS in the freshwater fish Australoheros facetus exposed to IMI and (2) to apply the IBR index to achieve a comprehensive understanding of OS in the fish. The results of the present study showed that all the biomarkers presented different responses in the three monitored tissues: liver, brain and gills. Results for an initial battery of 19 biomarkers were obtained and for the IBR index only those with significant differences have been considered. The biomarkers that had the most important weight on the IBR index were SOD activity in brain and gills, H2O2 concentration in liver, and carbonyl groups concentration in gills in fishes exposed to 100 and 1000 μg L−1 IMI. This index allowed affirming that a short term exposure to environmentally relevant concentrations of IMI (≥10 μg L−1) produces OS in A. facetus. However, a more deep understanding of some biomarkers response is necessary to improve the index and for finally apply it in field studies.